Qualitative and Quantitative Analysis of Idiopathic Macular Hole by SD-OCT-A Cross Sectional Study - Gyana Prasoona Devi Nookala; Jagannath Challa; Sai Priyanka; Sree Lakshmi Pallamreddy (JK Science)
Background: Idiopathic macular hole (IMH) is a condition characterized by anatomic discontinuity of the neurosensory retina in the fovea. Spectral-domain optical coherence tomography (SD-OCT) has emerged as the benchmark for diagnosing and assessing macular holes. Objective: The objective of this study was to assess qualitative and quantitative characteristics of IMH on OCT and explore their relationship with the staging of macular holes and the best-corrected visual acuity (BCVA). Methods: A cross-sectional observational study was carried out involving 30 patients diagnosed with IMH. Various qualitative and quantitative parameters were recorded using SD-OCT. Associations between these parameters, macular hole staging, and BCVA were analyzed statistically. Results: The study revealed a female predominance among IMH patients, full thickness macular hole (FTMH) being the most common stage. Mean BCVA decreased with increasing MH staging, and Significant correlations were identified among BCVA and qualitative characteristics such as loss of integrity of photoreceptor layer and intraretinal cysts. Quantitative parameters including macular hole base diameter (MHBD), macular hole height (MHH), and inner segment/outer segment (IS/OS) defect diameter showed significant differences across MH stages. Conclusion: Understanding qualitative and quantitative features observed via SD-OCT in IMH patients is essential for enhancing treatment approaches including preoperative planning, leading to better anatomical and functional prognoses and enhancing visual function.